Focal Osteoporotic Bone Marrow Defect of the Anterior Mandible: A Case Report : Focal Osteoporotic Bone Marrow Defect - Atarbashi-Moghadam, Saede; Lotfi, Ali (Regeneration, Reconstruction & Restoration (Triple R), 2024)
Focal osteoporotic bone marrow defect (FOBMD) of the jaw is a radiolucent lesion that usually occurs in the mandibular molar region of a middle-aged female. Incisional biopsy is recommended for definite diagnosis and then no further treatment is needed. The prognosis is excellent. This paper presents a 40-year-old female with an asymptomatic well-defined corticated radiolucency in the anterior of the mandible discovered incidentally in a dental checkup. Histopathologic examination showed a fatty marrow and the diagnosis of FOBMD was made. FOBMD is seldom included in the differential diagnosis of jaw radiolucencies; therefore, dental practitioners should be familiar with the clinical, radiographic, and microscopic characteristics of this entity.